Changing demand for maritime trade - Pierre Cariou (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper analyses the main drivers for maritime trade growth over the last decades and suggests possible drivers for the development of maritime trade in the future.
Keywords: 330; Frachtschifffahrt; Erfolgsfaktor; Branchenentwicklung